A polyphasic taxonomy analysis reveals the presence of an ecotype of Rahnella contaminans associated with the gut of Dendroctonus-bark beetles - Rivera-Orduña, Flor N.; Pineda-Mendoza, Rosa María; Vega-Correa, Brenda; López, María Fernanda; Cano-Ramírez, Claudia; Zhang, Xiao Xia; Chen, Wen Feng; Zúñiga, Gerardo (Frontiers in Microbiology, 2023)
Species belonging to the genus Rahnella are dominant members of the core gut bacteriome of Dendroctonus-bark beetles, a group of insects that includes the most destructive agents of pine forest in North and Central America, and Eurasia. From 300 isolates recovered from the gut of these beetles, ten were selected to describe an ecotype of Rahnella contaminans. The polyphasic approach conducted with these isolates included phenotypic characteristics, fatty acid analysis, 16S rRNA gene, multilocus sequence analyses (gyrB, rpoB, infB and atpD genes), and complete genome sequencing of two isolates, CdrAdgB13 and JaDmexAd06, representative of the studied set. Phenotypic characterization, chemotaxonomic analysis, phylogenetic analyses of the 16S rRNA gene and multilocus sequence analysis (MLSA) showed that these isolates belonged to Rahnella contaminans. The G + C content of the genome of ChdrAdgB13 and JaDmexAd06 was 52.8 and 52.9%, respectively, similar to those from other Rahnella species, including R. contaminans. The phylogenomic analysis showed that both strains integrated a consistent and well defined cluster, together with R. contaminans, within the Rahnella genus. The ANI between ChdrAdgB13 and JaDmexAd06 and Rahnella species varied from 84.02 to 99.18%, including R. contaminans. A noteworthy observation in this study is the presence of peritrichous flagella and fimbriae in these ecotypes. The in silico analysis of genes encoding the flagellar system of the strains ChdrAdgB13, JaDmexAd06 and Rahnella species showed the presence of flag-1 primary system encoding peritrichous flagella, as well as fimbriae genes from the families type 1, ,  and , mainly encoding chaperone/usher fimbriae, as well as other uncharacterized families. The results of this study showed that isolates from the gut of Dendrotonus-bark beetles are an ecotype of R. contaminans, which is dominant and persistent in all developmental stages in bark beetles and one of the main members of the core gut bacteriome of these insects.